2012
DOI: 10.1155/2012/136398
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Specific Prevalence of Risk Factors in Patients with First-Ever Ischemic Stroke in China

Abstract: Background. Evidences are accumulating that age and gender have great impact on the distribution of stroke risk factors. Such data are lacking in Chinese population. Methods. 1027 patients with first-ever ischemic stroke (IS) were recruited and divided into young adult (<50 years), middle-aged (50∼80 years), and very old (>80 years) groups according to stroke onset ages. Vascular risk factors were collected and compared among groups. Results. Female patients were globally older than male patients at stroke ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 27 publications
8
31
3
Order By: Relevance
“…Regarding age, many had the notion that older people have higher risk of stroke, and this is consistent with what literature has shown (Feigin et al, 2017;Zhang et al, 2012). Research showed that stroke incidence is higher among the elderly because they are more likely to have higher prevalence of classic vascular risk factors such as ischemic heart diseases, chronic heart failure, and atrial fibrillation, which build-up over time (Yao et al, 2012). Concerning the gender dynamics on risk relativity, while the male groups mentioned that men are more at risk of stroke, the female groups stated that women have higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding age, many had the notion that older people have higher risk of stroke, and this is consistent with what literature has shown (Feigin et al, 2017;Zhang et al, 2012). Research showed that stroke incidence is higher among the elderly because they are more likely to have higher prevalence of classic vascular risk factors such as ischemic heart diseases, chronic heart failure, and atrial fibrillation, which build-up over time (Yao et al, 2012). Concerning the gender dynamics on risk relativity, while the male groups mentioned that men are more at risk of stroke, the female groups stated that women have higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…[34, 35] An alternative explanation is that neuro-vascular risk factors are more frequent and severe in men and have declined faster in women, for example tobacco. [36, 37]…”
Section: Discussionmentioning
confidence: 99%
“…The differences in fall incidence rates between studies could be explained by differences in the characteristics of the stroke groups across studies (Weerdestyn et al., ). Considering the prevalence of stroke increases as a result of aging of the population (Ashburn et al., ; Yao et al., ), the fall rate could be partially explained by the age of the participants. The mean age of our participants was 63 years, which was below than that of the participants in the studies by Kerse et al.…”
Section: Discussionmentioning
confidence: 99%